Identification of Needs for Tutorial-based Electronic Modules (E-Modules) for Village Operators - Anryza, Anryza; Murwaningsih, Tri; Efendi, Agus (Social, Humanities, and Educational Studies (SHES): Conference Series, 2023)
Digitization in an information delivery system is a sign that the development of digital technology is getting faster and entering all aspects of life. There-fore, this study aims to identify various needs in the framework of develop-ing a tutorial-based electronic module (e-module) for Village operators to operate the SIAP Desa application. This research is a descriptive- quantitative research using a survey method, the research subjects consisted of 61 village operators with a non-test data collection technique accompanied by an in-strument, namely a questionnaire. The data analysis technique used is de-scriptive analysis technique with percentages. The research results show that village operators have a low level of understanding on how to operate the SIA P Desa application, even though most of them have attended training ac-tivities. They needed material that they could study in the form of text or video tutorials. Most of them then agreed that e-modules or electronic mod-ules were one of the efforts that could be made so that they could learn the material for operating the SIAP Desa application independently.